A cost-effectiveness analysis of shortened direct-acting antiviral treatment in genotype 1 noncirrhotic treatment-naive patients with chronic hepatitis C virus - Fawsitt, C; Vickerman, P; Cooke, G; Welton, N (Elsevier, 2019)
Background Direct-acting antivirals are successful in curing hepatitis C virus infection in more than 95% of patients treated for 12 weeks, but they are expensive. Shortened treatment durations, which may have lower cure rates, have been proposed to reduce costs. Objectives To evaluate the lifetime cost-effectiveness of different shortened treatment durations for genotype 1 noncirrhotic treatment-naive patients. Methods Assuming a UK National Health Service perspective, we used a probabilistic decision tree and Markov model to compare 3 unstratified shortened treatment durations (8, 6, and 4 weeks) against a standard 12-week treatment duration. Patients failing shortened first-line treatment were re-treated with a 12-week treatment regimen. Parameter inputs were taken from published studies. Results The 8-week treatment duration had an expected incremental net monetary benefit of £7737 (95% confidence interval £3242-£11 819) versus the standard 12-week treatment, per 1000 patients. The 6-week treatment had a positive incremental net monetary benefit, although some uncertainty was observed. The probability that the 8- and 6-week treatments were the most cost-effective was 56% and 25%, respectively, whereas that for the 4-week treatment was 17%. Results were generally robust to sensitivity analyses, including a threshold analysis that showed that the 8-week treatment was the most cost-effective at all drug prices lower than £40 000 per 12-week course. Conclusions Shortening treatments licensed for 12 weeks to 8 weeks is cost-effective in genotype 1 noncirrhotic treatment-naive patients. There was considerable uncertainty in the estimates for 6- and 4-week treatments, with some indication that the 6-week treatment may be cost-effective.